Precision measurements with kaon and pion decays at CERN - Bizzeti Andrea (EPJ Web of Conferences)
The NA62 measurement of the branching ratio and the di-photon mass spectrum of the K+ → π+γγ decay is presented, together with a preliminary result on the branching fraction of the rare decay π0 → e+e−. The first observation of the decay K±→π0π0 μ±v(K00μ4) by the NA48/2 experiment at the CERN is also reported, together with the measurement of the branching ratio.